Aboriginal Children's and Youths' Experiences of Bullying and Peer Victimization in a Canadian Context - Do, Cindy (2012)
Researchers have consistently shown that as a society, we have failed to protect a large number of Aboriginal children and youths from violence and aggression across multiple contexts. Aboriginal children and youth are at a disproportionate risk of being involved in violent victimization ranging from homicides, family violence, and physical and sexual abuse compared to the rest of Canadian children and youth. However, the extent to which Aboriginal children and youths are involved in bullying remain largely unknown. In the present study, data from a Canadian population-based study was used to examine ethnic and sex differences in children’s and youths’ involvement of different forms of bullying (general, physical, verbal, social). Participants were categorized into three broad ethnic groups: Aboriginal, Caucasian, and ethnic minority. Results indicated that across the forms of bullying, Aboriginal children and youths were more frequently involved than their non Aboriginal peers. Sex differences also emerged, such that, Aboriginal boys were more frequently physically victimized than their non Aboriginal, same sex peers while no ethnic group differences were found for girls. The results highlight the need for an Aboriginal-specific bullying policy and specialized programs and services at school to support this vulnerable group of Canadian school-aged children.